Angiosarcoma-like Kaposi Sarcoma: A Distinctive Histomorphologic Variant Representing an Important Diagnostic Pitfall. (11th December 2022) - Plaza, Jose A.; Sangueza, Omar P.; Giubellino, Alessio; Gru, Alejandro A.; Kaffenberger, Benjamin; Wakely, Paul E.; Sangueza, Martin J.
Abstract : Kaposi sarcoma (KS) is a rare low-grade angioproliferative neoplasm associated with human herpesvirus 8 (HHV-8) infection with multiple clinical subtypes and varying histopathologic patterns. Histologically, many different variants of KS have been reported, yet all can be difficult to recognize and must be differentiated from other vascular tumors. In this report, we studied fourteen cases of a newly described variant of KS reminiscent of a well-differentiated angiosarcoma (angiosarcoma-like KS). All cases showed a diffuse, ill-defined infiltrative dermal-based lesion composed of numerous anastomosing vascular channels of varying caliber lined by a single layer of endothelium with minimal pleomorphism. The vascular proliferation ramified through the dermis and dissected the collagen bundles along with infiltration into the subcutaneous fat and around skin appendages. All cases showed expression of vascular markers (CD31, CD34, and ERG) and were positive for HHV-8. None showed the classic histopathology associated with KS. Without clinical guidance these tumors can be difficult to recognize as KS, creating significant diagnostic challenges. Our study expands on a rare histologic variant of KS that ought to be considered in the differential diagnosis of any cutaneous well-differentiated angiosarcoma. Awareness of this variant of KS is of important for proper diagnosis and management of these patients; thus, careful attention to the histomorphology and clinical history can help lead the pathologist to the correct diagnosis.